Biomechanical Analysis of Shooting Technique and Body Position in Extracurricular Football Students - ibnu nasikhi; Tommy Soenyoto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze shooting skills based on technique and body position when kicking using a biomechanical approach in extracurricular soccer students at SMA Negeri 1 Purbalingga. The method used is descriptive quantitative, data collection through video recordings was analyzed using Kinovea software and then processed using IBM SPSS. The research sample consisted of 10 students using a purposive sampling technique. The variables in this study were body tilt, support foot position, and kick accuracy. The results showed an average body tilt of 39.70°, support foot position of 36.00°, and kick accuracy of 127.0860 cm with quite high variations in each variable. Biomechanically, body tilt is related to body balance, while the position of the support foot plays a role in determining the direction of the force that affects kick accuracy. The biomechanical approach based on video analysis can be used as a reference in evaluating techniques and designing more targeted training to improve body balance, technical consistency, and student kick accuracy.